Headquarters-Subsidiary Exchanges and the Quality of Headquarters-Subsidiary Relationship - Li, J.; Jiang, Fuming; Travaglione, Tony (Strategic Management Society, 2015)
Through the lens of the social exchange theory, we developed and empirically tested a theoretical framework that contextualizes the effects of two levels of headquarters-subsidiary exchange on quality of headquarters-subsidiary relationship, and how subsidiary manager’s organizational identity, parent’s ownership in subsidiary, and subsidiary’s entry mode interact with these exchanges in shaping the quality of headquarters-subsidiary relationship. Survey data from 305 Chinese MNEs found that managerial and organizational exchanges have positive influences on the quality of headquarters-subsidiary relationship. It also found that the positive influence of managerial exchange is weakened when the subsidiary manager has a stronger organizational identity with subsidiary, and the positive influence of organizational exchange is weakened when subsidiary is wholly owned by parent and the subsidiary is established via greenfield entry mode.